The E3 ubiquitin ligase Nedd4/Nedd4L is directly regulated by microRNA 1. - Zhu, J.Y.; Heidersbach, A.; Kathiriya, I.S.; Garay, B.I.; Ivey, K.N.; Srivastava, D.; Han, Z.; King, I.N. (Development, 2017)
miR-1 is a small noncoding RNA molecule that modulates gene expression in heart and skeletal muscle. Loss of Drosophila miR-1 produces defects in somatic muscle and embryonic heart development, which have been partly attributed to miR-1 directly targeting Delta to decrease Notch signaling. Here, we show that overexpression of miR-1 in the fly wing can paradoxically increase Notch activity independently of its effects on Delta. Analyses of potential miR-1 targets revealed that miR-1 directly regulates the 3'UTR of the E3 ubiquitin ligase Nedd4 Analysis of embryonic and adult fly heart revealed that the Nedd4 protein regulates heart development in Drosophila Larval fly hearts overexpressing miR-1 have profound defects in actin filament organization that are partially rescued by concurrent overexpression of Nedd4. These results indicate that miR-1 and Nedd4 act together in the formation and actin-dependent patterning of the fly heart. Importantly, we have found that the biochemical and genetic relationship between miR-1 and the mammalian ortholog Nedd4-like (Nedd4l) is evolutionarily conserved in the mammalian heart, potentially indicating a role for Nedd4L in mammalian postnatal maturation. Thus, miR-1-mediated regulation of Nedd4/Nedd4L expression may serve to broadly modulate the trafficking or degradation of Nedd4/Nedd4L substrates in the heart.